Coverage and activity management of wireless video sensor networks for surveillance applications. (5th April 2012) - Pham, Congduc
Wireless Video Sensor Networks consist in nodes with miniaturised cameras. Unlike omni–directional sensors, the sensing region of a video node is limited to the field of view of its camera. This paper addresses the issues of building an intrusion detection system based on these video sensors and presents two contributions. The first contribution presents the performance of various cover set construction strategies for determining for each sensor its level of redundancy. Simulation results showed the performance of the strategies in terms of percentage of coverage, network lifetime, intrusion stealth time and number of intrusion detection. The second contribution addresses efficient activity management of nodes for mission–critical surveillance applications. The proposed approach dynamically determines a sensor's frame capture rate. We showed that varying the criticality level dynamically during the network operation increases the network lifetime while maintaining a high level of service. With reinforcement behaviour the network lifetime is further increased.